(untitled) (CIPEEX, 2025)
INTRODUCTION: Obsessive-Compulsive Disorder (OCD) is a chronic psychiatric condition characterized by the presence of obsessions and compulsions that typically cause distress, consume time, and interfere with the individual’s daily routine. The contents of obsessions usually include fears of contamination, unwanted aggressive thoughts, the need for symmetry, and taboos related to sex or religion. Screen time refers to the duration of time spent using electronic devices, social media, and televisions. Thus, it is crucial to analyze how current technology may influence OCD. OBJECTIVE: To describe how screen time can contribute to the development of Obsessive-Compulsive Disorder (OCD) in children. METHODOLOGY: A systematic review was conducted using the PICo strategy. Databases such as PubMed, Scielo, and Google Scholar were searched using the health science descriptors in English: “Screen Time,” “Children,” and “Obsessive-Compulsive Disorder,” with the Boolean operator AND. Four articles published in the last 5 years and available in full online were selected. RESULTS: Studies have shown that increased screen time is closely related to the development of recently onset OCD, with each additional hour of daily screen time contributing to the disorder’s development. The main activities linked to OCD development are video gaming and watching videos on YouTube. Video games can lead to the development of perfectionism due to the need to achieve certain records or to an overestimation of threat due to constant exposure to screen violence, both of which are key symptoms of the disorder. Regarding YouTube videos, they can trigger negative self-perceptions in children when comparing themselves to digital influencers and provide easy access to compulsive viewing of homogeneous content, potentially leading to obsession, a classic feature of the condition. CONCLUSION: It was evident that screen time is closely related to the increase in OCD cases among children. This is because technology triggers perfectionism, low self-esteem, compulsivity, and aggressive thoughts in children, which are primary symptoms of the disorder. Thus, it becomes clear that early introduction of screens in children’s lives increases the risk of developing Obsessive-Compulsive Disorder.